A evolução do mercado de capitais brasileiro e sua popularização - Lima, Francisco Starley Patrício (2010)
Reports the factors that contributed to the development of Brazilian capital markets in recent years and the importance of this follow-up for fundraising by companies. Describes concepts of financial market and capital market and explains the entire structure that gives sustenance and support this market. Conceptualization regulators and self-regulators that create the standards that are applied in the market, and execute them. Discusses the relationship between investrs and securities market, emphasizing the new idea to change the culture of Brasilians who only sought the savings account as an alternative source of new revenues. Emphasizes the importance of advances in technology and communications for the dissemination of the capital market ant the improvements achieved in the operations at the market. Shows how the globalization process and legislative reform was essential to the capital markets evolve in Brazil and how that market is helping the growth and development of the country.